Evaluation of learning English with the illuminative model in the Fun English program - Risa Ginting (Curricula: Journal of Curriculum Development, 2023)
English is an international language used by almost all countries, one of which is Indonesia. English is also very important to learn because it can be used to communicate with many people in various countries. This study aims to determine the level of students' learning skills in English conversation classes, to measure the level of effectiveness of the Fun English program in developing students' English skills, as well as to make improvements and improvements to the Fun English learning program, which is evaluated using the illuminative model. This study used the literature study method, and data collection was carried out using direct observation techniques in the Fun English program. The participants in this study were English course leaders, teachers, and students who participated in an English conversation practice program. The study results show that the learning evaluation implemented in the Fun English program is effective enough to measure students' English proficiency. The Fun English program is quite effective in developing students' English conversation skills, especially in listening, speaking, pronunciation, and fluency.   Abstrak Bahasa Inggris merupakan bahasa internasional yang digunakan oleh hampir semua negara, salah satunya adalah Indonesia. Bahasa Inggris juga sangat penting untuk dipelajari karena dapat digunakan sebagai alat komunikasi dengan banyak orang pada berbagai macam negara. Penelitian ini bertujuan untuk mengetahui tingkat kecakapan belajar para siswa dalam kelas percakapan bahasa Inggris, mengukur tingkat efektivitas program Fun English dalam mengembangkan kemampuan berbahasa Inggris siswa, serta untuk melakukan perbaikan dan penyempurnaan program pembelajaran Fun English yang di evaluasi menggunakan model iluminatif. Penelitian ini menggunakan metode studi pustaka dan pengumpulan data dilakukan dengan teknik observasi secara langsung pada program Fun English. Partisipan dalam penelitian ini adalah pimpinan kursus bahasa Inggris, guru, dan murid-murid yang mengikuti program latihan percakapan bahasa Inggris. Hasil penelitian menunjukkan bahwa evaluasi pembelajaran yang diterapkan dalam program Fun English ini sudah cukup efektif untuk mengukur kemampuan berbahasa Inggris siswa. Program Fun English ini cukup efektif untuk mengembangkan kemampuan percakapan siswa dalam bahasa Inggris khususnya dalam aspek menyimak, berbicara, pelafalan, dan kelancaran. Kata Kunci: evaluasi pembelajaran; fun English; model illuminatif; pembelajaran Bahasa Inggris